Volunteer Engagement and Retention among New and Past UK Mental Health Charity Helpline Volunteers: A Longitudinal Qualitative Study - Rosanna May Maletta; Victoria Vass; Eric Robinson (Voluntas: International Journal of Voluntary and Nonprofit Organizations, 2026)
Abstract Voluntary mental health support services play an important role in public health. However, long-term retention of volunteers is a major challenge. The present study aimed to understand the reasons for reduced volunteer engagement and retention loss in a UK mental health charity. Twenty-two participants from two populations (new volunteers and leavers) were engaged in semi-structured interviews to (1) longitudinally explore new volunteers’ expectations and experiences in their new role; and (2) explore reasons for stopping volunteering. Using constructivist grounded theory, we found key barriers to engagement among volunteers in this sector: unmet needs and values, unclear or demanding commitments, and reduced confidence in the role. Addressing these barriers through clearer expectations, stronger social connection, and processes that build confidence and coping (e.g., additional training) may enhance engagement and retention. Our findings suggest areas where targeted adjustments could enhance volunteer engagement and retention.